2017
DOI: 10.3390/min8010006
|View full text |Cite
|
Sign up to set email alerts
|

Natural Radioactivity of Intrusive-Metamorphic and Sedimentary Rocks of the Balkan Mountain Range (Serbia, Stara Planina)

Abstract: Stara Planina (also known as the Balkan mountain range) is known for numerous occurrences and deposits of uranium and associated radionuclides. It is also famous for its geodiversity. The geologic framework is highly complex. The mountain is situated between the latitudes of 43 • and 44 • N and the longitudes from 22 • 16 to 23 • 00 E. Uranium exploration and radioactivity testing on Stara Planina began back in 1948. Uranium has also been mined in the zone of Kalna, within the Janja granite intrusive. The natu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, the p XRF and XRD result for pyrite-graphite-quartz schist does not show a significantly higher percentage of radioactive minerals and radionuclides than mudstone, which is probably due to the heterogeneity of accessory minerals and radioactive isotopes. Abdulqader et al ( 2018 ) also observed that the schist sample with higher graphitic content also contains more uranium. However, quartz in metamorphic rocks can show insignificant radioactivity (Manjunatha et al 2013 ).…”
Section: Discussionmentioning
confidence: 94%
“…However, the p XRF and XRD result for pyrite-graphite-quartz schist does not show a significantly higher percentage of radioactive minerals and radionuclides than mudstone, which is probably due to the heterogeneity of accessory minerals and radioactive isotopes. Abdulqader et al ( 2018 ) also observed that the schist sample with higher graphitic content also contains more uranium. However, quartz in metamorphic rocks can show insignificant radioactivity (Manjunatha et al 2013 ).…”
Section: Discussionmentioning
confidence: 94%
“…According to the HPGe measurement result, Mamuju is an anomalous area because it has high contents of 238 (Figure 6) [21]. This shows that Mamuju has potential as an exploration area for radioactive minerals if we compare these values with other studies [22][23][24]. According to the HPGe measurement result, Mamuju is an anomalous area because it has high contents of 238 (Figure 6) [21].…”
Section: Among the Rees There Is A Positive Correlation Between Ypo mentioning
confidence: 95%